Development and characterization of stretchable conductive composites for sustainable and energy-efficient electronic applications - Ramli, Mizah; Mokhtar, Nur Hazwani; Nordin, Mohd Nur Azmi; Zakaria, Mohamad Shukri; Md Ghazaly, Mariam; Mohd Yusof, Mohd Haaziq (Italian Association of Chemical Engineering (AIDIC), 2025)
Stretchable conductive composite (SCC) has emerged as a promising material for flexible electronic applications. This study investigates the formulation, mechanical behaviors, and functional performance of SCC composed of graphene nanoplatelets (GNPs) and poly (3,4-ethylenedioxythiophene) polystyrene sulfonate (PEDOT:PSS), deposited on thermoplastic polyurethane (TPU). During the optimization of mixing parameters, three different configurations were studied: low-speed mixing at 400 rpm for 10 minutes, medium-speed mixing at 1500 rpm for 30 minutes, and high-speed mixing at 2000 rpm for 60 minutes. A mixing speed of 400 rpm for 10 minutes yielded the lowest sheet resistivity, indicating optimal dispersion. Surface treatments using methyl ethyl ketone (MEK) and an adhesion promoter significantly enhanced conductivity, suggesting improved film uniformity and filler–substrate interaction. Under cyclic loading at room temperature, 40 °C, and 80 °C, the SCC exhibited gradual changes in strain and resistivity. The optimized SCC with mixing parameter at 400 rpm for 10 minutes and coated with adhesion promoter showed the lowest sheet resistance of 3 Ω/sq. At 80 °C and after 30 cycles, the SCC displayed about a 3.8 % increase in strain capacity accompanied by higher resistivity that indicates reduced electrical stability. LEDs connected with SCC showed slightly lower brightness than those with wire connections at low voltages because of higher resistance. However, at 20 V they achieved a similar peak brightness (~41,000 cd/m²), demonstrating that SCC can work effectively as a flexible interconnect. This work demonstrates the feasibility of developing thermally stable SCC through optimized formulation and processing strategies.